EPIDEMIOLOGICAL ANALYSIS OF CARIES IN CHILDREN DURING OUT-PATIENT TREATMENT IN DONETSK REGION - A. V. Makhniova (Український стоматологічний альманах, 2018)
Relevance. Frequency of tooth decay in children doesn’t have a tendency to decline. Frequency of turning to the therapeutic stomatological clinic concerning caries is 40-50 % of the general amount of patients. Frequency of the complicated temporary teeth caries in children under 7 was 37.3 %. Growth of prevalence of the complicated temporary teeth caries in children seeking stomatological treatment increased from 9.1 % to 69.1 %.